Measuring Research Productivity of Universities with Centre with Potential for Excellence in Particular Area (CPEPA) status in Karnataka State - Kappi, Mallikarjun; M., Chaman Sab; Biradar, B S (DESIDOC Journal of Library & Information Technology, 2021)
This paper aims to track the research output of the ‘Universities with CPEPA status in Karnataka’ during 2010–2019 as considering the Web of Science database. The Karnatak University, Dharwad, Bangalore University, Bangalore, and the University of Mysore, Mysore have been selected. A total of 8952 documents have been retrieved consisting of journal articles, conference papers, book chapters, so on. A steady increase in research output has been observed. The University of Mysore (UMM) has the largest number of publications. The study shows that multi-authored papers have greater research influence in receiving citations. The study found the most productive authors and their production impacts in terms of the number of citations (ACPP) and also identified the most occurred keywords and journals used to publishing the research results. For visualisation purposes, VOSviewer and Bibliometrix R Package were used.